The Kurds Are in The Book Zubdat Alnasrat Wanukhbat Alensra, "The History of the Series Seljoukid." Bondari "(643 AH / 1245 A.D.) - Musa Mohammed Khidhir (QALAAI ZANIST JOURNAL, 2020)
Al-Fath bin Ali bin Muhammad Al-Bandari Al-Isfahani 586-AH / 1190-1245 CE, the author and summary of this book (Zubdat Alnasrat Wanukhbat Alnasra,) is the prominent scientist and jurist in the seventh century AH / thirteenth century AD. Al-Bandari paid much attention to the works of (Imad Al-Din Kateb Al-Isfahani 519-597 AH / 1125-1200 A.D.), including the book (Zubdat Alnasrat Wanukhbat Alnasra), which was dedicated to the history of the Seljuks and their ministers, and added to them with footnotes. Although this book contains historical information from the beginning of the Seljuk era and 140 years of their rule, the aim of this research is to show several aspects of the history of the Kurds, because Kurdish names, personalities and leaders came in this book in generosity, and he also mentioned about the role of the Kurds In important historical events, such as: The reception of the Kurdish prince (Nasr bin Marwan) to the Alb Arslan of the Seljuk and the events of the castle of Amad, and the relationship of the prince (Hazar Asb) with Tughrbelk and the Seljuks, also, he mentioned rare events on the leadership of the Ayyubid and the Kurdish principalities, using the historical method in this research relying on the aforementioned book and comparing it with contemporary and late historical sources.